Effectiveness of E-Module Teaching Material Development in Learning Procedure Text Using Flip Pdf For SMP Students - Pertiwi, Nidia Harum; Widodo, Mulyanto; Ariyani, Farida; Sumarti, Sumarti; Samhati, Siti (UNDIKMA, 2025)
This research aims to develop and evaluate the effectiveness of Flip PDF-based e-modules in learning procedure texts at junior high school level grade VII. The use of the ADDIE approach is the basis for the stages of analysis, design, development, implementation, and product evaluation. The assessment results show that this e-module is suitable for use in the teaching and learning process with a score of 80.3%, because it is able to facilitate understanding of the material, increase learning motivation, and is visually appealing and interactive. The evaluation also identified the need for improvement, such as adjusting the content to the local context and adding technical guidelines. The results of this study are expected to contribute to the development of effective and innovative technology-based learning media in improving learners' literacy skills, especially in understanding procedure texts